Combining web‐based tools for transparent evaluation of data for risk assessment: developmental effects of bisphenol A on the mammary gland as a case study. Issue 3 (4th August 2016) - Molander, Linda; Hanberg, Annika; Rudén, Christina; Ågerstrand, Marlene; Beronius, Anna
Abstract : Different tools have been developed that facilitate systematic and transparent evaluation and handling of toxicity data in the risk assessment process. The present paper sets out to explore the combined use of two web‐based tools for study evaluation and identification of reliable data relevant to health risk assessment. For this purpose, a case study was performed using in vivo toxicity studies investigating low‐dose effects of bisphenol A on mammary gland development. The reliability of the mammary gland studies was evaluated using the Science in Risk Assessment and Policy (SciRAP) criteria for toxicity studies. The Health Assessment Workspace Collaborative (HAWC) was used for characterizing and visualizing the mammary gland data in terms of type of effects investigated and reported, and the distribution of these effects within the dose interval. It was then investigated whether there was any relationship between study reliability and the type of effects reported and/or their distribution in the dose interval. The combination of the SciRAP and HAWC tools allowed for transparent evaluation and visualization of the studies investigating developmental effects of BPA on the mammary gland. The use of these tools showed that there were no apparent differences in the type of effects and their distribution in the dose interval between the five studies assessed as most reliable and the whole data set. Combining the SciRAP and HAWC tools was found to be a useful approach for evaluating in vivo toxicity studies and identifying reliable and sensitive information relevant to regulatory risk assessment of chemicals. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : The present paper explores the combined use of the Science in Risk Assessment and Policy toxicity study evaluation method and the Health Assessment Workspace Collaborative tools for identification of reliable data relevant to health risk assessment. Combining the Science in Risk Assessment and Policy and Health Assessment Workspace Collaborative tools was found to be a useful and transparent approach for evaluating in vivo toxicity studies and identifying reliable and sensitive information relevant to regulatory risk assessment of chemicals.